Mobilizing a Social Justice Agenda. Issue 2 (1st July 2019) - Mitchell, Claudia
Abstract : As this issue of Girlhood Studies went to press, two very dramatic moments in the history of girls and young women were in the public eye. One was the large 8000-strong gathering of NGOs, researchers, politicians, and activists from 165 countries at the Women Deliver Global Summit on gender equality that took place in Vancouver, Canada, from 3 to 6 June 2019. There, according the program, the focus was on how power can both hinder and drive progress and change for a world that is more gender equal. On 3 June, the long-awaited report of the National Inquiry into Missing and Murdered Indigenous Women and Girls (MMIWG) in Canada was released, with its 231 recommendations or calls for social justice to address what is now acknowledged as being part of what was (and continues to be) cultural genocide. Both the Global Summit and the report on MMIWG are reminders of the need for the blend of scholarship and activism that is so critical to advancing issues of equity and to implementing recommendations to achieve this. This unthemed issue with its broad range of geographic locations, concerns, and methods and its attention to activism, along with scholarship that features work from both the humanities and social sciences, is key in relation to mobilizing a social justice agenda.